1971
DOI: 10.2135/cropsci1971.0011183x001100040035x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance in Soybeans to the lvlexican Bean Beetle. I. Sources of Resistance1

Abstract: World collections of soybean, Glycine max (L.) Merr., maturity groups VII and VIII, were screened for resistance to the Mexican bean beetle, Epilachna varivestis Mulsant, in 1968. Twenty‐three selections and five commercial cuhivars were intensively studied in 1969. In the field plants of PI 229358, PI 171451, and PI 227687 were highly resistant. Laboratory forced feeding tests showed that these three lines, were unsatisfactory as food even when no alternate food was available. Of the commercial lines tested ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 0 publications
2
48
0
3
Order By: Relevance
“…Rareness at SSR loci, especially in plants with rare alleles at multiple loci, may indicate that these landraces have had limited genetic exchange with other landraces, and therefore may have rare alleles for various (functional) traits as well. As genetic improvement of a trait often involves Wnding useful variants which may be present at a low frequency (Chamberlain and Bernard 1968;Van Duyn et al 1971;Anand and Gallo 1984;Anand et al 1988; Coordinative Group of Evaluation of SCN 1993), this could be a means of identifying plants with possible useful alleles. Hyten et al (2006) found that 79% of the low-frequency sequence variants in the Asian Landrace collection were not present in the elite cultivars, which suggests that the variation useful for genetic improvement is not yet present in the elite cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Rareness at SSR loci, especially in plants with rare alleles at multiple loci, may indicate that these landraces have had limited genetic exchange with other landraces, and therefore may have rare alleles for various (functional) traits as well. As genetic improvement of a trait often involves Wnding useful variants which may be present at a low frequency (Chamberlain and Bernard 1968;Van Duyn et al 1971;Anand and Gallo 1984;Anand et al 1988; Coordinative Group of Evaluation of SCN 1993), this could be a means of identifying plants with possible useful alleles. Hyten et al (2006) found that 79% of the low-frequency sequence variants in the Asian Landrace collection were not present in the elite cultivars, which suggests that the variation useful for genetic improvement is not yet present in the elite cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1970s, three soybean cultivars (PI171451: 'Kosamame'; PI227687: 'Miyako White'; PI229358: 'Sodendaizu') were reported to have resistance to Mexican bean beetle (Epilachna varivestis Mulsant) (Van Duyn et al 1971). They were also found to have resistance to other herbivorous insects, including Spodoptera species (Hatchett et al 1976, Lambert andKilen 1984a).…”
Section: Introductionmentioning
confidence: 99%
“…The search for such resistant germplasms began in the 1960s in the United States. Initially, three plant introduction (PI) lines from Japan (PI229358, PI227687 and PI171451) were shown to exhibit resistance to the Mexican bean beetle [Epilachna varivestis (Mulsant)] 50 . These lines were confirmed to have resistance to other herbivorous insects.…”
Section: Genetic Resources For Resistance To Herbivorous Insectsmentioning
confidence: 99%
“…When the breeding program to develop CCW-resistant soybean in Japan started in 1977, some genetic resources resistant to some lepidopteran herbivorous insects had been reported in the United States 50 . The screening of CCW-resistant germplasms in Japan took advantage of these preceding studies.…”
Section: Genetic Resources For Resistance To Herbivorous Insectsmentioning
confidence: 99%